Application of Monopoly Game Media In Learning Mathematical Counting Operations Grade 3 MIM Talang - Mahendra, Fiqih Jaya; Sukartono, Sukartono (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2023)
This study aims to describe how the application of monopoly game media in mathematical arithmetic operations learning in class III MIM Talang. This type of research is descriptive qualitative research. The research subjects were III grade students. Data collection techniques using interviews, observation, and documentation. The validity of the data using the method triangulation technique. After the collected data were analyzed using Miles and Huberman interactive analysis techniques. The results showed that planning mathematics learning by applying monopoly game media was carried out by preparing a lesson plan, monopoly game materials, and designing a series of monopoly game activities. The application of this monopoly game media received a positive response from students. Supporting factors for the application of monopoly game media to mathematical arithmetic operations include: the basic materials for making monopoly are easy to obtain and inexpensive, students actively participate, there is support from the school, and students feel like they are playing while learning. While the inhibiting factors include: class conditions that are not conducive because there are some students who are busy alone, students have difficulty answering the questions on the monopoly card, and time constraints. Solutions to overcoming these obstacles include: the teacher needs to recognize student characteristics, the teacher does ice breaking, students ask the teacher about difficulties answering questions, choose questions that are more focused and relevant to fit the existing time limit, and the teacher holds class sessions to help students who need understanding of the material.